Effective communication skills starts with #hellomynameis - Idris, Faridah; Adam, Siti Khadijah; Hod, Rafidah (Penerbit Universiti Sains Malaysia, 2023)
Effective communication is a fundamental element in a good doctor and health care professional (HCP) relationship as good communication skills among HCPs have been demonstrated to increase patient compliance and safety. The aspect of self-introduction and greeting during communication with patients and caregivers may be taken lightly by some doctors and HCPs, which can negatively impact the building of therapeutic relationships in any clinical interaction. This article briefly addresses and re-emphasises the importance of self-introduction for doctors and HCPs during their communication with patients, with the highlight on the #hellomynameis campaign and ways to practice it during the pandemic.